Regulation of MicroRNAs-Mediated Autophagic Flux: A New Regulatory Avenue for Neurodegenerative Diseases With Focus on Prion Diseases - Shah, Syed Zahid Ali; Zhao, Deming; Hussain, Tariq; Sabir, Naveed; Yang, Lifeng (Frontiers in Aging Neuroscience, 2018)
Prion diseases are fatal neurological disorders affecting various mammalian species including humans. Lack of proper diagnostic tools and non-availability of therapeutic remedies are hindering the control strategies for prion diseases. MicroRNAs (miRNAs) are abundant endogenous short non-coding essential RNA molecules that negatively regulate the target genes after transcription. Several biological processes depend on miRNAs, and altered profiles of these miRNAs are potential biomarkers for various neurodegenerative diseases, including prion diseases. Autophagic flux degrades the misfolded prion proteins to reduce chronic endoplasmic reticulum stress and enhance cell survival. Recent evidence suggests that specific miRNAs target and regulate the autophagic mechanism, which is critical for alleviating cellular stress. miRNAs-mediated regulation of these specific proteins involved in the autophagy represents a new target with highly significant therapeutic prospects. Here, we will briefly describe the biology of miRNAs, the use of miRNAs as potential biomarkers with their credibility, the regulatory mechanism of miRNAs in major neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and prion diseases, degradation pathways for aggregated prion proteins, the role of autophagy in prion diseases. Finally, we will discuss the miRNAs-modulated autophagic flux in neurodegenerative diseases and employ them as potential therapeutic intervention strategy in prion diseases.